Influence Store Atmosphere and Word of Mouth on The Purchase Decision with Interest to Buy as Intervening Variable - Nur Aini Parwitasari; Yana Sonjaya; Edi Tedi; Megie Ambarsari; Nur Ahmad Ruyani (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2023)
This study aims to examine the effect of Store Atmosphere and Word of Mouth on purchasing decisions with purchase intention as an intervening variable. This study uses quantitative data types, namely data measured on a numerical scale. The population is the number of Daily Fresh visitors for the period November 2021 to November 2022 of 51,460 people. The data collection technique uses nonprobability sampling and the number of samples is 100 respondents. In addition, the data analysis technique uses path analysis using SPSS. The results of the study concluded that Store Atmosphere had a positive and significant effect on purchase intention, Word of Mouth had a positive and significant effect on purchase intention, Store Atmosphere and Word of Mouth simultaneously had a positive and significant effect on purchase intention, purchase intention had a positive and significant effect on purchasing decisions , Store Atmosphere has a positive and significant effect on purchasing decisions, Word of Mouth has a positive and significant effect on purchasing decisions, buying interest has a positive and significant effect mediating Store Atmosphere on purchasing decisions, and buying interest has a positive and significant effect mediating Word of Mouth on purchasing decisions on Daily Fresh consumers.